Portable power supply design with 100 Watt capacity - Azriyenni Azhari Zakri; Almasdi Syahza; Dirman Hanafi; Hanggun Syahadat (invotek, 2021)
Renewable energy from solar cells is a type of alternative energy for consumers, especially those far from electricity, and saves electrical energy. This research developed an innovative tool for portable solar power generators as a source of energy, which stores electrical energy in two ways, namely solar cells and transformers. Furthermore, this research is expected to improve innovation tools for more efficient electricity supply and energy use, especially for rural communities. It also uses a variety of battery capacities to test portable power supplies. The results showed that the power supply using 100 Wp solar cells produced a capacity of 20 Ah, 60 Ah, and 100 Ah on the battery. Charging with a solar energy source on a 20 Ah battery takes a duration of 5 hours to be fully charged, while 60 Ah and 100 Ah batteries cannot be fully charged in one day. Charging a battery that has been run at a full level takes a duration of 15 hours at a temperature of 30oC to 34oC. Finally, this tool is expected to add variety to locally manufactured products.